OSTEOLOGY AND RELATIONSHIPS OF THE SPANKH MACKERELS AND SEERFISHES OF THE TRIBE SCOMBEROMORINI - Devaraj, M (Indian Journal of Fisheries, 2011)
Scomberomorus chtnensis appears intermediate between AeanthocyHium andthe other species of Scomberomorus as well as a primitive species of .the genusfrom which two groups of seeriisbes diverged, the cavalla group consisting of S.commenon and J, cavalla, aiid the guttatus group consisting of S. guttatus, S.koreanus, S. linecdafus, S. maculatus and'5. regalis. Within the latter group, S.guttatus and S. koreanus are more closely related to each other. S. lineolatuspossesses 'many characteristics intermediate, between the two groups. The cavallagroup is very closely related to Acanthocybium and the major difterenoe lies in thevertebral count. Specialized characters ot each species are pointed out.